Subtype-Specific Off-Label Treatment of Rosacea - Nita Wienholtz; Messoud Ashina; Jacob P. Thyssen; Alexander Egeberg (Karger Publishers, 2021)
We present 2 cases of rosacea that were successfully managed with off-label treatment. The first is a case of painful, exuding papulopustular lesions of the nose treated with rifaximin, and the other is a case of severe, debilitating and painful flushing treated with sumatriptan. The cases support previous notions that gastrointestinal comorbidities may be related to papulopustular lesions and that flushing may be related to neurogenic inflammation and migraine. The cases also imply that a new approach to rosacea management, based on endotypes and comorbidities, may be warranted.